Get a job : labor markets, economic opportunity, and crime - Crutchfield, Robert D. (New perspectives in crime, deviance, and law series., 2014)
Are the unemployed more likely to commit crimes? Does having a job make one less likely to commit a crime? Criminologists have found that individuals who are marginalized from the labor market are more likely to commit crimes, and communities with more members who are marginal to the labor market have higher rates of crime. Yet, as Robert Crutchfield explains, contrary to popular expectations, unemployment has been found to be an inconsistent predictor of either individual criminality or collective crime rates. In Get a Job, Crutchfield offers a carefully nuanced understanding of the links a.